Dampak Kebebasan Pers Di Sumatera Barat Pascareformasi - Mardikola Tri Rahmad (Hadharah: Jurnal Keislaman dan Peradaban, 2020)
Freedom Of the press that happened after reformation in Indonesia gives a good news for industry in this country, including West Sumatera. The Impact for press company, that easily to get a permission, a freedom to criticize the goverment, meeting, and association. But, this freedom has negative impact, among of them is busines competition between press company and domination of enterpreneurs as a capital  owner each of press company too high. While for public, the positive impect for the freedom of the press  that giving information is opened, motivates the change in mindset of people, attitude and motivates a change in culture of people. And the negative impect is couse a crisis moral, spread a bad news or hoax, appearing pornography content, and raising business competition among press company.